Privatization of Government Enterprise: The Challenge to Management - Hadi, Achmad Setyo (Forum Manajemen; Vol 13 No 68 (1999): Forum Manajemen Prasetiya Mulya | November 1999, 1999)
The decade of the eighties will be recorded as the period when governments throughout the world embarked on an ambitious program to transfer ownership of governments enterprise to the private sector. The magnitude of this change in ownership structure is enormous: the World Bank reports over 80 nations have programs underway involving the transfer of ownership of thousands of government owned enterprise. This process, called privatization, will have significant impact on how these enterprises are managed, the goals and objectives they pursue, and the task environment of managerial decisions. It is an emerging public policy that will affect the managerial decision process in these and related enterprises for the foreseeable future. Management scholars will be unable to ignore the effects of privatization in the study of competitive strategy, social issues, and employee relations.